Miconia indicoviolacea (Melastomataceae: Miconieae): a new Colombian species from the western flanks of the cordillera Occidental - Gamba, Diana; Almeda, Frank; Alvear, Marcela (Phytotaxa, 2014)
Miconia indicoviolacea is described from the western slopes of the western cordillera in the Chocó biogeographic region of Colombia, illustrated, and compared with superficially similar species that are also endemic to the country. It is readily recognized by its prevailingly purple to dark blue inflorescence branches, peduncles, and internodes, minute glandular-puberulent vegetative and hypanthial indumentum, caudate foliar apex, dorsally inclined anther pores, glabrous rounded to truncate dorso-basal staminal appendages, and seeds with a conspicuous appendage at the chalazal end and a raphal zone that is approximately double the size of the seed corpus.